Enhancing stress corrosion cracking resistance of low Cu-containing Al-Zn-Mg-Cu alloys by slow quench rate. (15th February 2019) - Yuan, Dingling; Chen, Kanghua; SongyiChen,; Zhou, Liang; Chang, Jiangyu; Huang, Lanping; Yi, Youping
Abstract: The corrosion behavior of Al-Zn-Mg-Cu alloy on different Cu content and quench rate has been investigated by inter-granular corrosion (IGC), exfoliation corrosion (EXCO), and stress corrosion cracking (SCC) test, and combined with scanning electron microscopy (SEM) and transmission electron microscopy-energy dispersive spectrometer (TEM-EDS) microstructural observation. The results showed that slow quench rate can effectively improve the SCC resistance of low Cu-containing alloys, especially decreasing crack propagation rate (the SCC propagation velocity (VII ) is about an order of magnitude lower for slowly-quenched low Cu-containing alloys than fast quenched one), while it has less effect on high Cu-containing alloys. The IGC, EXCO, and SCC resistance with different Cu content and quench rate are analyzed by distribution, size and Cu content of grain boundary precipitates and width of precipitate-free zone. The corrosion mechanism has been studied in detail. Graphical abstract: Highlights: Corrosion resistance is greatly affected by microchemistry and distribution of precipitates. Slow rate quench can effectively improve stress corrosion cracking resistance of low Cu-containing alloys. The corrosion mechanism under the influence of Cu content and quench rate has been investigated.